Wayward. Volume six, Bound to fate - Zub, Jim (Image Comics, Inc., 2018)
"The final battle is here! Teenagers face off against the supernatural creatures of Japan as Wayward comes to its brutal, breathtaking conclusion. 'Bound to Fate' is a sweeping finale filled with action, drama, and pathos as destiny and power collide--and nothing will ever be the same."-- <U+01C2>c Provided by publisher.